Down-regulated miR-124-3p enhanced the migration and epithelial-stromal transformation of endometrial stromal cells extracted from eutopic endometrium in subjects with adenomyosis by up-regulating Neuropilin 1. (April 2021) - Huang, Nan; Xu, Liyan; Qiu, Yafen; Zhan, Jinlai; Chen, Xiangjun
Highlights: MiR-124−3p was down-regulated in adenomyosis endometrial. NRP1 was up-regulated in adenomyosis endometrial. MiR-124−3p regulated the viability, migration, and EMT in ESCs. MiR-124−3p targeted NRP1. The effects of miR-124−3p on ESCs was mediated by regulating NRP1. Abstract: MiR-124−3p regulates the biological function of endometrial cancer cells. However, the role of miR-124−3p in adenomyosis (AM) has not been reported. Hence, we hypothesized that miR-124−3p also regulated the development of AM. The expressions of miR-124−3p and Neuropilin 1 (NRP1) in AM endometrial tissues were evaluated by Quantitative Real-time-PCR (qPCR). Endometrial stromal cells (ESCs) were isolated from the eutopic endometrial tissue of women with AM and further identified using immunofluorescence. Then the target of miR-124−3p was predicted by Starbase V2.0 and verified by dual-luciferase assay. After transfection of miR-124−3p mimic, inhibitor, or NRP1 overexpression plasmids, the viability and migration of ESCs were measured by Cell counting kit -8 (CCK-8) and wound healing assays, respectively. The expressions of NRP1 and epithelial-stromal transformation (EST)-related factors were evaluated by Quantitative Real-time-PCR (qPCR) or Western blot. MiR-124−3p was down-regulated and NRP1 was up-regulated in AM eutopic endometrial tissues. NRP1 was targeted by miR-124−3p. The extracted ESCs were Vimentin-positive and Cytokeratin-negative. MiR-124−3p mimic decreased viability, migration, and the expressions of NRP1, Vimentin, N-cadherin, and matrix metalloproteinase (MMP-9) in ESCs while increasing the expression of E-cadherin. MiR-124−3p inhibitor and NRP1 overexpression had the contrary effect of miR-124−3p on ESCs. Furthermore, NRP1 overexpression offset the effect of miR-124−3p mimic on viability, migration, and expressions of NRP1 and EMT-related factors in ESCs. MiR-124−3p regulated the migration and EMT of ESCs by down-regulating NRP1.